Interfacing ecology and policy: Developing an ecological framework and evidence base to support wildfire management in South Africa. (23rd October 2013) - Le Maitre, David C.; Kruger, Fred J.; Forsyth, Greg G.
Abstract This paper describes the first step in developing an approach to fire risk assessment aimed at balancing the reduction of risks to lives and livelihoods and maintaining fire regimes which protect ecosystem biodiversity and function in fire‐prone ecosystems. Wildfires pose a major hazard to people's lives, livelihoods and ecosystems in South Africa with poor communities generally being highly exposed and vulnerable. Although general information exists, an adequate understanding of the fire regimes, how they vary spatially, and the related vegetation management requirements is lacking. This study resolves the environmental variation in fire regimes across South Africa into a systematic framework for wildfire risk assessment and ecologically sound ecosystem management. The available descriptions of fire regimes, vegetation classifications, and fire occurrence data from remote sensing are synthesized to derive a set of 13 distinct fire‐ecology types, that is, sets of vegetation units which experience distinct fire regimes. Fuel dynamics, fire‐dependence, ecologically acceptable fire regimes, and guidelines for fire management are described for each of these fire‐ecology types and they are grouped into three categories: fire dependent, fire independent and fire sensitive. Fire‐dependent ecosystems comprise more than 60% of South Africa and fire‐independent ones 32%, the latter mainly in the arid west and northwest, while the remainder are fire sensitive. Fire‐dependent systems require fires and generally coincide with the greatest rural population densities. The outputs from this framework can be used to analyse wildfire risk and translate the risk into practical management measures which are responsive to local ecological, social and institutional settings.